Comparative proteomic analysis of the effects of high-concentrate diet on the hepatic metabolism and inflammatory response in lactating dairy goats - Duanmu, Yongqian (J Anim Sci Biotechnol, 2016)
BACKGROUND: To understand the impact of feeding a high-concentrate diet to mid-lactating goats for a long time on liver metabolism and inflammatory response, two dimensional polyacrylamide gel electrophoresis (2-DE) and real-time PCR method were employed to detect proteins differentially expressed in liver and their mRNAs expression in goats fed high concentrate diet (HC) or low concentrate diet (LC). Twelve lactating dairy goats were randomly assigned to either a HC diet group (65 % concentrate of dry matter; n = 6) or a LC diet group (35 % concentrate of dry matter; n = 6) for 10 wk. RESULTS: Twenty differentially expressed spots (≥2.0-fold changes) in the hepatic tissues were excised and successfully identified using MALDI TOF/TOF. Of these, 8 proteins were up-regulated, while the rest 12 proteins were down-regulated in HC goats compared to LC. Differential expressed proteins including alpha enolase 1 (ENO1), glutamate dehydrogenase 1 (GLUD1), glutathione S-transferase A1 (GSTA1), ATP synthase subunit 5β (ATP5β), superoxide dismutase [Cu-Zn] (SOD1), cytochrom c oxidase subunit Via (COX6A1) and heat shock protein 60 (HSP60) were further verified by real-time PCR and/or western blot at mRNA or protein expression level. Consistent with the 2-DE results, a significant decrease of β-actin protein expression and SOD enzyme activity was observed in liver of HC goats (P < 0.05), while ENO1 protein expression was significantly up-regulated in HC compared to LC goats (P < 0.05) . However, western blot analysis did not show a significant difference of hepatic HSP60 protein between HC and LC group, which did not match the decrease of HSP60 content detected by 2-DE analysis. Real-time PCR showed that glutathione S-transferase P1 (GSTP1) and SOD1 mRNA expression was significantly decreased in liver of HC goats, while cytochrom c oxidase (COX3) and ATPase 8 (ATP8) mRNAs expression were markedly increased compared to LC (P < 0.05). Gene Ontology (GO) analysis revealed that HC diet resulted in altered expression of proteins related to catalytic and mitochondrial metabolism in the liver, and may increase the stress response with up-regulating the expression of differentiation 14 (CD14) cluster and serum amyloid A (SAA) as well as C-reactive protein (CRP) in the liver. CONCLUSIONS: These results suggest that feeding high concentrate diet to lactating goats for 10 wk leads to the activation of the inflammatory response, and decreases the anti-oxidant capacity, and subsequently impairs the mitochondrial function in the liver. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40104-016-0065-0) contains supplementary material, which is available to authorized users.